Discovery of an extended X-ray jet in AP librae - Kaufmann, S.; Wagner, S.; Tibolla, Omar (Institute of Physics Publishing, Inc., 2013)
Chandra observations of the low-energy-peaked BL Lac object (LBL) AP Librae (AP Lib) revealed the clear discovery of a non-thermal X-ray jet. AP Lib is the first LBL with an extended non-thermal X-ray jet that shows emission into the very high energy range. The X-ray jet has an extension of ~15''(˜ 14 kpc). The X-ray jet morphology is similar to the radio jet observed with Very Large Array at 1.36 GHz emerging in the southeast direction and bends by 50° at a distance of 12'' toward the northeast. The intensity profiles of the X-ray emission studied are consistent with those found in the radio range. The spectral analysis reveals that the X-ray spectra of the core and jet region are both inverse-Compton-(IC)-dominated. This adds to a still small sample of BL Lac objects whose X-ray jets are IC-dominated and thus more similar to the high-luminosity Fanaroff-Riley II sources than to the low-luminosity Fanaroff-Riley I objects, which are usually considered to be the parent population of BL Lac objects.